Digital Competency Gaps and Professional Development of Archivists in Indonesia Across Functional Career Levels - Jalinur; Wira Sakinatun Najahah; Asma Rakha’ Dinazzah; Rahmi (Record and Library Journal, 2026)
Background of the study: Archives serve as strategic information resources that support decision-making, organizational memory, and public accountability. As digital transformation continues to reshape archival practices, understanding and developing the professional competencies of archivists is crucial for maintaining these vital resources. Purpose: This study analyzes the competencies of Indonesian archivists across three domains—managerial, socio-cultural, and technical. Method: Using a descriptive quantitative approach, data were collected through an online questionnaire based on the KemenPANRB competency standards (2022), involving 68 respondents, primarily from Java and Sumatra. Findings: The findings reveal that archivists generally demonstrate high levels of competency across all domains; technical competencies appear relatively consistent across functional levels, while managerial and socio-cultural competencies are more prominent at senior levels. Importantly, a gap in digital-related archival skills was identified across all career stages. Conclusion: In conclusion, the study highlights the necessity of implementing tiered professional development pathways that align closely with archivists' specific functional positions. Additionally, it emphasizes the urgent requirement to systematically strengthen digital competencies to ensure profession-wide resilience against accelerating digital transformation.